Heterozygous Hemoglobin Sherwood Forest Causing Polycythemia - Raghunathan, Vikram M.; Butera, James N.; Treaba, Diana O. (Case Reports in Hematology, 2017)
Hemoglobin (Hb) Sherwood Forest is a rare high-affinity hemoglobin first described in 1977, arising from an Arg to Thr substitution at codon 104 of the beta chain. This hemoglobin variant has been identified in few individuals and has been associated with a compensatory erythrocytosis in the homozygous state. Prior scarce case reports have noted that heterozygotes for this variant are phenotypically normal. Here we present a patient who was evaluated in our hematology clinic for chronic erythrocytosis and was found to be heterozygous for Hb Sherwood Forest. No other primary or secondary cause of his polycythemia was identified. This is the first described case of heterozygous Hemoglobin Sherwood Forest causing erythrocytosis.